Inhibition of the histone H3K27 demethylase UTX enhances tumor cell radiosensitivity - Rath, Barbara H. (Mol Cancer Ther, 2018)
The processes mediating the repair of DNA double strand breaks (DSBs) are critical determinants of radiosensitivity and provide a source of potential targets for tumor radiosensitization. Among the events required for efficient DSB repair are a variety of post-translational histone modifications including methylation. Because trimethylation of histone H3 on lysine 27 (H3K27me3) has been associated with chromatin condensation, which can influence DSB repair, we determined the effects of radiation on H3K27me3 levels in tumor and normal cell lines. Irradiation of tumor cells resulted in a rapid loss of H3K27me3, which was prevented by the siRNA-mediated knockdown of the H3K27 demethylase UTX. Knockdown of UTX also enhanced the radiosensitivity of each tumor cell line. Treatment of tumor cells with the H3K27 demethylase inhibitor GSKJ4 immediately before irradiation prevented the radiation-induced decrease in H3K27me3 and enhanced radiosensitivity. As determined by neutral comet analysis and γH2AX expression, this GSKJ4 treatment protocol inhibited the repair of radiation-induced DSBs. Consistent with in vitro results, treatment of mice bearing leg tumor xenografts with GSKJ4 significantly enhance radiation-induce tumor growth delay. In contrast to results generated from tumor cell lines, radiation had no effect on H3K27me3 levels in normal fibroblast cell lines and GSKJ4 did not enhance their radiosensitivity. These data suggest that H3K27me3 demethylation contributes to DSB repair in tumor cells and that UTX, the demethylase responsible, provides a target for selective tumor cell radiosensitization.